Optimization of carbon and nitrogen medium components for biomass production using non‐Saccharomyces wine yeasts. (11th February 2014) - Schnierda, T.; Bauer, F. F.; Divol, B.; van, E.; Görgens, J. F.
Abstract The impact of different nitrogen and carbon sources on biomass production of the non‐Saccharomyces wine yeast species Lachancea thermotolerans, Metschnikowia pulcherrima and Issatchenkia orientalis was assessed. Using a molasses‐based medium, yeast extract and corn steep liquor as well as ammonium sulphate and di‐ammonium phosphate (DAP) as nitrogen sources were compared in shake‐flask cultures. A medium with 20 g l−1 sugar (diluted molasses) and 500 mg l−1 total yeast assimilable nitrogen, from yeast extract, gave the highest biomass concentrations and yields. Invertase pretreatment was required for cultures of M. pulcherrima and I. orientalis, and respective biomass yields of 0·7 and 0·8 g g−1 were achieved in aerobic bioreactor cultures. The absence of ethanol production suggested Crabtree‐negative behaviour by these yeasts, whereas Crabtree‐positive behaviour by L. thermotolerans resulted in ethanol and biomass concentrations of 5·5 and 11·1 g l−1, respectively. Significance and Impact of the Study Recent studies demonstrate that non‐Saccharomyces yeasts confer positive attributes to the final composition of wine. However, optimal process conditions for their biomass production have not been described, thereby limiting commercial application. In this study, industrial media and methods of yeast cultivation were investigated to develop protocols for biomass production of non‐Saccharomyces yeast starter cultures for the wine industry.